The formative process of the Mapuche socio-cultural system (TRIM. Tordesillas, revista de investigación multidisciplinar, 2019)
Along the centuriesdifferent theories have been proposed to elucidate the origin of the mapuche people, without considering, usually, the possibility that they were originally from the current chilean territory. In the present paper we expose these theories to, finally, analyze with the current scientific knowledge the formative process of the mapuche socio-cultural system.
Keywords: Mapuches; Origins; debates; Pitrén; El Vergel